Immunomodulatory innate defence regulator (IDR) peptide alleviates airway inflammation and hyper-responsiveness. Issue 10 (31st May 2018) - Piyadasa, Hadeesha; Hemshekhar, Mahadevappa; Altieri, Anthony; Basu, Sujata; van der Does, Anne M; Halayko, Andrew J; Hiemstra, Pieter S; Mookherjee, Neeloffer
Abstract : Background: Exacerbation in asthma is associated with decreased expression of specific host defence peptides (HDPs) in the lungs. We examined the effects of a synthetic derivative of HDP, innate defence regulator (IDR) peptide IDR-1002, in house dust mite (HDM)-challenged murine model of asthma, in interleukin (IL)-33-challenged mice and in human primary bronchial epithelial cells (PBECs). Methods: IDR-1002 (6 mg/kg per mouse) was administered (subcutaneously) in HDM-challenged and/or IL-33-challenged BALB/c mice. Lung function analysis was performed with increasing dose of methacholine by flexi Vent small animal ventilator, cell differentials in bronchoalveolar lavage performed by modified Wright-Giemsa staining, and cytokines monitored by MesoScale Discovery assay and ELISA. PBECs stimulated with tumour necrosis factor alpha (TNF-α) and interferon gamma (IFN-γ), with or without IDR-1002, were analysed by western blots. Results: IDR-1002 blunted HDM challenge-induced airway hyper-responsiveness (AHR), and lung leucocyte accumulation including that of eosinophils and neutrophils, in HDM-challenged mice. Concomitantly, IDR-1002 suppressed HDM-induced IL-33 in the lungs. IFN-γ/TNF-α-induced IL-33 production was abrogated by IDR-1002 in PBECs. Administration of IL-33 in HDM-challenged mice, or challenge with IL-33 alone, mitigated the ability of IDR-1002 to control leucocyte accumulation in the lungs, suggesting that the suppression of IL-33 is essential for the anti-inflammatory activity of IDR-1002. In contrast, the peptide significantly reduced either HDM, IL-33 or HDM+IL-33 co-challenge-induced AHR in vivo. Conclusion: This study demonstrates that an immunomodulatory IDR peptide controls the pathophysiology of asthma in a murine model. As IL-33 is implicated in steroid-refractory severe asthma, our findings on the effects of IDR-1002 may contribute to the development of novel therapies for steroid-refractory severe asthma.